Pemurnian Ethanol Secara Destilasi Dengan Penambahan Garam KCl - Abas Sato; Adi Rahardianto; Andy Bagoes Santoso (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2015)
One of the methods of ethanol mixture separation is distilation with addition of potassium chloride salt as entrainer. The aim of this research is to determine the effect of salt additiont and the reflux ratio, to ethanol product concentration, and also determine the best operating condition of the highest ethanol concentration in the distillation product. The material used in the research are ethanol, potassium chloride and water. Equipment used is a series of sieve tray type distillation tower in diameter of 2.5 inch. Variable used in this research are: potassium chloride salt addition (0; 5; 10) grams/liter of alcohol solution, the concentration of ethanol feed (10; 50; 90) weight percent and reflux ratio (0,5; 1; 1.5 ), the fixed variable are ethanol feed in 4th tray, the flow rate (1250 ml/min), destillation time (120 minutes), and the number of sieve tray (11 trays). The research were carried out by introducing ethanol in specific concentration into the feed storage and reboiler and also potassium chloride into the salt storage. The reboiler is heated until evaporation of ethanol occur and distillation were carried out. Ethanol as product of distillation are measured its volume and concentration. The result is that the highest ethanol concentration is 98% by concentration of feed (50-90)%, addition of potassium chloride salt of 10 g rams/ liter, and reflux ratio of 1.5.